Performance of composite structural insulated panel with metal skin subjected to blast loading - Chen, Wensu; Hao, Hong; Chen, Shuyang; Hernandez, F. (Elsevier, 2015)
Structural insulated panel (SIP) is a lightweight composite panel used in a wide range of commercial, industrial and residential building industry. It consists of insulating polymer foam sandwiched by two layers of structural skins. The composite structural insulated panel is considered as a sustainable, economical, thermal insulated, moisture resistant, acoustic insulated and flame retardant panel, which has been more and more commonly used in building industry, and also in petrochemical industry for construction of office buildings, control rooms, store rooms and residential structures. These structures might be subjected to far field explosion loads caused by accidental gas explosion in residential areas and Vapour cloud explosion (VCE) in petroleum and chemical processing industries. The performance of composite structural insulated panel against accidental explosions has yet been investigated. In this study, the blast resistant performance of the composite panel is numerically investigated by using software LS-DYNA with the calibrated numerical model. Its blast resistance capacity and energy absorption capacity is quantitatively examined. Parametric studies are also carried out to investigate the effect of panel configurations on its blast resistance capacity.